Verbascum misirdalianum (Scrophulariaceae), a new species from central Anatolia, Turkey - Çeçen, Ömer; Karaveli̇oğullari, Fai̇k Ahmet; Ünal, Ayvaz (Phytotaxa, 2015)
Verbascum misirdalianum (Scrophulariaceae) is described and illustrated as a new species endemic to central Anatolia, Turkey. In this study, diagnostic morphological characters of this new species and closely related species (V. tossiense) are discussed. Furthermore, comments on habitat, morphology and conservation status are provided and distribution maps presented for the two taxa.